Implementing a Payment Gateway in the Mount Slamet Hiking Ticketing System - Bahy, Faishal; Arif, Dani; Amin, M. Syaiful (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Background—Many hiking basecamps in Indonesia still process bookings manually, causing queues, quota uncertainty, and errors in payment verification that hinder operations. Objective— Design and implement a web-based information system (e-ticketing) for Mount Slamet hiking, integrated with the Midtrans payment gateway; validate transactions in near-real-time and issue ticket IDs for gate inspection. Methods—Development followed Agile/Scrum. Requirements were gathered through observation and interviews; the design employed use-case, activity, ERD, and payment-flow models. Implementation used React (UI), Express and Prisma ORM (API), MySQL, and Midtrans Snap, with signature-verified, idempotent webhooks. Trials covered end-to-end black-box testing (booking; transitions among pending, paid, expired, and canceled; ticket-ID issuance; and check-in), cross-browser compatibility (Chrome, Edge, Firefox, Safari on desktop and mobile), and the System Usability Scale (SUS; n = 13). We also monitored propagation time from settlement to order update and behavior in the admin panel (route, quota, and date-closure management). Results—All functional scenarios passed; behavior was consistent across major browsers; mean SUS = 75.0 (> 68) indicates acceptable usability. Webhooks ensured automatic, duplicate-free status updates, with propagation on the order of seconds, so the reservation–payment–e-ticket chain operated end-to-end and was traceable via ticket-ID logs. Conclusion—The proposed e-ticketing system is technically feasible for basecamp operations and provides an architectural blueprint, core data schema, and a replicable Midtrans integration pattern. Future work will refine the public interface, add refund/void features, and conduct production-grade performance and security testing.